1992
DOI: 10.1021/es00027a021
|View full text |Cite
|
Sign up to set email alerts
|

Transport and separation of organic macromolecules in ultrafiltration processes

Abstract: The membrane transport and separation characteristics of natural humic macromolecules and a model polyelectrolyte, polystyrene sulfonate), in ultrafiltration systems employing hydrophilic, neutral, cellulosic-type membranes were studied. The application of a permeation model based on membrane flux equations was systematically validated for charged, random-coil polymers. It was possible to characterize transport behavior of various solute/membrane combinations by a single membrane permeation factor, which was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
81
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(86 citation statements)
references
References 31 publications
4
81
0
1
Order By: Relevance
“…We have not observed large changes in watercolumn trace metal partitioning between colloidal and dissolved forms that could have been attributed to salinity changes (Wen et al 1996(Wen et al , 1997b(Wen et al , 1999. Kilduff and Weber (1992) and Logan and Jiang (1990) demonstrated that ionic strength changes would mainly affect lower molecular weight forms with molecular weights in the neighborhood of the molecular weight cutoff of the cartridge, i.e., in our case, 1 kDa.…”
mentioning
confidence: 48%
“…We have not observed large changes in watercolumn trace metal partitioning between colloidal and dissolved forms that could have been attributed to salinity changes (Wen et al 1996(Wen et al , 1997b(Wen et al , 1999. Kilduff and Weber (1992) and Logan and Jiang (1990) demonstrated that ionic strength changes would mainly affect lower molecular weight forms with molecular weights in the neighborhood of the molecular weight cutoff of the cartridge, i.e., in our case, 1 kDa.…”
mentioning
confidence: 48%
“…This may be due to changes in RC with Ž . cf, as discussed by Kilduff and Weber 1992 . If the same trend continues, we would expect 126 mM and 285 mM OC at cfs 20 and cf s 50, respectively Ž .…”
Section: Permeation Coefficient Modelmentioning
confidence: 89%
“…out . The CFF membrane science literature and freshwater CFF studies have long ad-Ž dressed this issue more rigorously Logan and Jiang, 1990;Kilduff and Weber, 1992;Douglas et al, . Ž .…”
Section: Background On Cff Breakthroughmentioning
confidence: 99%
“…Previous work from this same study demonstrated logarithmic permeation of DOC and Δ 14 C with increasing CF and thus increasing average MW of the retentate solution . These seawater DOC solutions were therefore shown to behave ideally with respect to UF theory [Cheryan, 1998;Kilduff and Weber, 1992] and not affected by membrane fouling, changes in permeation flow rates, or system pressures. Accordingly, the logarithmic permeation of DOC and Δ 14 C may also suggest logarithmic DOC size-age distributions.…”
Section: Doc Molecular Size-age Distribution Ultrafiltration Modelmentioning
confidence: 95%